Sistem Boarding School dalam Meningkatkan Pembinaan Akhlak di Pondok Pesantren Hasan Al-Massyath Nahdatul Wathon Gunung Sesang Terara: The Boarding School System in Improving Moral Development at the Hasan Al-Massyath Nahdatul Wathon Gunung Sesang Terara Islamic Boarding School - Syahdan; Sirajun Nasihin; Fitri Aulia (Al-Gafari : Manajemen dan Pendidikan, 2025)
Islamic boarding schools (Pondok Pesantren) are a type of Islamic educational institution that is unique to Indonesia. The term "Pondok Pesantren" is unique to Indonesia and not found in other Islamic countries. This study aims to explore how the boarding school system at Pondok Pesantren Hasan Al-Mahsyat Nahdatul Wathon Gunung Sesang Terara contributes to the development of students' character and morality (akhlak). The research focuses on three main questions: (1) how the boarding school system is implemented to enhance moral education, (2) how parents respond to the program, and (3) what impact it has on students’ character. A qualitative approach was used, employing interviews, observation, and documentation as data collection techniques. The findings indicate that the boarding school system significantly contributes to the moral development of students. This is reflected in six key points: parents’ motivation for choosing Islamic boarding school education, the effectiveness of religious practices and daily routines in instilling discipline and responsibility, positive behavioral changes in students, challenges such as differences in students’ backgrounds and the influence of social media, the exemplary role of teachers and caregivers, and expectations for system development that includes spiritual, life skills, and family collaboration aspects. These findings affirm that the boarding school system in pesantren can serve as a holistic and sustainable model for character education.